(untitled) (Khairulummah, 2024)
This research explores the Shari’ah-based justification for granting pardon, reduction, or suspension in discretionary (Ta‘zīr) punishments, in light of the objectives of Islamic law (Maqāṣid al-Sharī‘ah). Ta‘zīr refers to punishments where judges or rulers are given flexible authority within defined boundaries. The study seeks to identify under what conditions leniency is permissible, and to what extent such leniency aligns with the higher objectives of Shari‘ah—namely the protection of life, intellect, wealth, religion, and progeny. It also critically examines the modern state’s authority (e.g., presidential pardon) from an Islamic legal perspective. The findings suggest that while Islamic law does allow for mitigation or pardon in Ta‘zīr cases, such actions must adhere to the principles of justice, reform, and public interest. Unwarranted pardons, especially those driven by political motives, can undermine the very objectives of Shari‘ah and erode public trust in justice.